Best practices in a tiered approach to metabolite quantification: views and recommendations of the European Bioanalysis Forum. (July 2010) - Anders Kall, Morten; Gordon, Ben; Laakso, Sirpa; Freisleben, Achim; Hucker, Richard; Fischmann, Stephanie; Globig, Susanne; Sennbro, Carl-Johan; Jansat, Josep M; Mulder, Hans; Thomas, Elizabeth; Brundy-Kloeppel, Margrete; et al.
The relationship between the exposure to drug metabolites and overall drug safety has become an integral part of the drug-development process. In-depth discussions in the scientific community, as well as recent guidelines on Drug Safety Testing of Metabolites from the US FDA (often referred to as the MIST guidance and ICH M3(R2) from the International Conference on Harmonization (ICH), has brought clarity to the regulatory requirements of the sponsor company in providing documentation on circulating levels of qualifying metabolites. However, less attention has been given to the challenges now faced by the bioanalytical community in supporting these new guidance policies. In this paper, the European Bioanalysis Forum (EBF) is providing a recommendation on which quality standards to apply when assessing the (relative) abundance or absolute concentrations of metabolites. This paper is the result of both an intensive consultation within the EBF (through internal surveys amongst EBF member companies and discussions) and consultation of the broader bioanalytical community (through discussions at international conferences). These recommendations will provide an increased understanding of how to apply a tiered approach to metabolite quantification as part of the bioanalytical strategy. As such, it aims to provide support to the bioanalytical community on the appropriate level of validation required at each stage of the drug-development process.